2017
DOI: 10.1371/journal.pone.0170485
|View full text |Cite
|
Sign up to set email alerts
|

Thalassemia in the United Arab Emirates: Why it can be prevented but not eradicated

Abstract: Thalassemia is a genetic blood disorder that causes abnormal hemoglobin. Hemoglobin is a protein in red blood cells that carries oxygen and is made of two proteins from four α-globin genes and two β-globin genes. A defect in one or more of these genes causes thalassemia. The treatment of thalassemia mostly depends on life-long blood transfusions and removal of excessive iron from the blood stream. Such tremendous blood consumption puts pressure on the national blood stock in many countries. In particular, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…Furthermore, consanguinity is prevalent in the GCC region, which increases the risk of genetic-related health outcomes such as thalassemia [124] that can negatively impact pregnancy and child birth [125]. However, early intervention and management can minimize the negative consequences of these conditions on the delivery of the child and their prognosis.…”
Section: Gaps In Evidencementioning
confidence: 99%
“…Furthermore, consanguinity is prevalent in the GCC region, which increases the risk of genetic-related health outcomes such as thalassemia [124] that can negatively impact pregnancy and child birth [125]. However, early intervention and management can minimize the negative consequences of these conditions on the delivery of the child and their prognosis.…”
Section: Gaps In Evidencementioning
confidence: 99%
“…Cochran sample size calculation was dependent on the proportion of dental caries among β -thalassemia patients from previous studies in a comparable community in the region (82.6% in age group 6-9 and 78.6% in age group [12][13][14][15][16][17][18]. The data used in this study were published by Hattab et al 8 This yielded a minimum of 35 thalassemia patients required.…”
Section: Mater Ials and Methodsmentioning
confidence: 99%
“…At a population level, it was concluded that the prevention measures can only contribute to the reduction of the prevalence of the disease in the short term but not eradicate the disease. 14 The prevalence of dental caries and other orofacial conditions in thalassemia patients is not adequately reported in the UAE Emirati population and neighboring countries.…”
Section: U B a I β -T H A L A S S E M I A C H I L D R E N ' S O R Amentioning
confidence: 99%
See 2 more Smart Citations